DAMPAK 7-DAY RESERVE REPO RATE BANK INDONESIA DAN NILAI TUKAR RUPIAH TERHADAP PROFITABILITAS PERBANKAN PRIODE 2017-2019 - Salihin, Agus (Islamic Economics Program, Faculty of Islamic Economics and Business, 2020)
The purpose of this study was to determine the Impact of the 7-Day Reserve Repo Rate of Bank Indonesia and the Rupiah Exchange Rate on the Profitability of the 2017-2019 Banking Period